Treść umowy kontrzakupu w międzynarodowym obrocie handlowym - Olejniczak, Adam (Wydział Prawa i Administracji UAM, 1988)
Counterpurchase contract is one of more frequently concluded countertrade transactions in international trade. Like other countertrade transactions, it is not separately regulated in Polish law. The basis of any attempts to systematize these phenomena and to examine their legal character must be the analysis of their contents. In particular, the analysis of stipulations of a counterpurchase contract, i.e. a specific and characteristic type of such transactions, should be carried out. The author defines a counterpurchase contract as a type of a countertrade transaction in which the exporter obliges himself to purchase from the importer, or from any other person indicated by the latter, goods for the value being usually in proportion to the cost of the export transaction. In his article the author analyses: the stipulation of a counterpurchase contract formulating the duty to conclude in future the execution contracts — the indication of the volume of an obligation, type of goods and prices (sec. 3), clauses typical for international trade contracts — reexport clause, binding force clause, arbitration clause and property clause (sec. 4), stipulations determining the performance of an obligation — time limit, the certificate releasing from the obligation (sec. 5), indications of legal consequences of non-performance — stipulated penalties and the consequences of paying them.
The contens of counterpurchase contract in international trade